At risk : (Routledge, 2004)
The term "natural disaster" is often used to refer to natural events such as earthquakes, hurricanes, or floods. However, the phrase suggests an uncritical acceptance of a deeply engrained ideological and cultural myth. At Risk questions this myth and argues that extreme natural events are not disasters until a vulnerable group of people is exposed.